Investigation of Corrosion Resistance of Reinforced Concrete Structures with Varying Supplementary Cementitious Materials in Marine Infrastructure - Puspasari, Aisyah Dwi; Komara, Indra; Setyawan, Hendry; Susilo, Tri (Institut Teknologi Adhi Tama Surabaya, 2024)
The degradation of concrete strength may occur due to extreme environmental factors such as sea or coastal areas. Those factors can decrease the durability level of concrete structure signified by the corrosion of reinforced concrete structure. The use of fly ash as a concrete mixture is expected to minimize corrosion in concrete structures. Since fly ash has small particles, it can fill small voids in concrete and minimize corrosive substances. The investigation parameters in this study employed two types of corrosion acceleration test modelling using a 15x15x15cm cube tested object with a concrete quality of 40 MPa. Meanwhile, fly ash involves classes F and C within the level of 20% as well as applied corrosion prediction by 10% and 20%. The addition of fly ash to the concrete mixture can reduce the mass loss of reinforced concrete. The maximum mass loss on a normal test object with a corrosion prediction of 20% was obtained at 18.22%, while a 20% corrosion prediction obtained the smallest value for the SCMFA-C test object at 17.04%. The 20% corrosion prediction obtained the largest distribution of 0.355 mm on the normal test object and the smallest distribution of 0.299 mm occurred on the SCMFA-F test object. Thus, the addition of fly ash to the concrete mixture can reduce the distribution of corrosion and mass loss in reinforced concrete.